Miłość do stworzeń na kartach Biblii - Waldemar Chrostowski (Nicolaus Copernicus University in Toruń, 2011)
Rare theological considerations devoted to animals are in a sharp contrast with their place and role in the world and human life. Theologians mostly have stressed their mentioning in biblical accounts of the creation of world (Gen 1-2), as well as have condemned the different forms of bad actions towards them, but there is a lack of specifically Christian considerations based on the God's plan of salvation as realized by Jesus Christ. The author considers four points: 1. The need for deepening of Christian concept of Creation, possible thanks to the respect for the Incarnation; 2. Better understanding and imitation of Jesus Christ, especially as concerns our moral obligations and duties towards animals; 3. Theological reconsideration of the problem of animal's suffering; 4. The ethical and moral reconsideration of the commandment of love.